2000
DOI: 10.1080/096382800296755
|View full text |Cite
|
Sign up to set email alerts
|

The social impact of multiple sclerosis - a study of 305 patients and their relatives

Abstract: MS has a profound impact on the patients' social roles and their relatives' well-being. In contrast to previous studies, a high divorce/separation rate among patients with MS was not observed. Severe disability and cognitive impairment are predictors of loss of employment, decline in the standards of living and withdrawal from social and leisure activities among patients and are strong indicators of stress among relatives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
193
5
5

Year Published

2004
2004
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 263 publications
(215 citation statements)
references
References 17 publications
12
193
5
5
Order By: Relevance
“…Previous research has demonstrated that the ability to maintain a paid job is related to the severity of the disease and cognitive function. 20 Findings from this study indicated that those in the "essential group" were significantly less mobile and independent and received significantly more assistance than those in the "less essential" group, as well as perceiving assistance to be more significantly more essential. These findings suggest that this group may have had a more severe form of MS. Once again these findings support those of research from other countries.…”
Section: Discussionmentioning
confidence: 75%
“…Previous research has demonstrated that the ability to maintain a paid job is related to the severity of the disease and cognitive function. 20 Findings from this study indicated that those in the "essential group" were significantly less mobile and independent and received significantly more assistance than those in the "less essential" group, as well as perceiving assistance to be more significantly more essential. These findings suggest that this group may have had a more severe form of MS. Once again these findings support those of research from other countries.…”
Section: Discussionmentioning
confidence: 75%
“…Most researchers suggest that MS has a negative impact on relationships and satisfaction with the romantic relationship is lower than in the general population 20,21,22 . Health professionals should be aware of the high rates of SD and low levels of sexual satisfaction among individuals with MS.…”
Section: Discussionmentioning
confidence: 99%
“…Looking beyond the obvious discomfort and functional limitations that illness brings about, many studies have shown that people with chronic health problems often experience a shrinkage of social roles, withdrawal from valued occupations, loss of choice and control over lifestyle, and threats to self and identity (e.g. 7,8,9). People whose illness necessitates early retirement often feel cut off from their usual sources of pride, accomplishment and self-esteem (10).…”
Section: Some Key Challenges Of Living With Long-term Illnessmentioning
confidence: 99%